A STUDY OF SPERM DEFORMITY INDEX AT ISLAMABAD - Ahmad, Muhammad Owais; Tariq, Muhammad (Pakistan Journal of Physiology, 2011)
Background: The aim of this study was to determine the sperm deformity index (SDI) of proven fertile males and compare this with that of infertile males. Methods: The study was carried out at Islamic International Medical College Rawalpindi and Islamabad Clinic Serving Infertile Couples, Islamabad, from July 2005 to July 2006. It was a cross-sectional comparative study. Fifty healthy fertile males were selected, another 50 infertile males were inducted as controls. The sampling technique was convenience non-probability. Their sperm morphology was determined according to Tygerberg’s strict criteria and the SDI was calculated. Inclusion criterion for proven fertile males was pregnancy achieved within 1 year of marriage with successful coituses. In case of infertile males it was failure to achieve pregnancy without the use of assisted reproductive techniques, with no infertility factors in the female partner. The semen samples were obtained at the laboratory after 3 to 4 days of sexual abstinence with clear written and oral instructions given to the subjects. Results: The infertile group was found to be significantly older than the proven fertile group (36.60±6.28 versus 31.32±6.10 years, p<0.000). SDI was significantly less in the proven fertile group (p<0.007). SDI ranged from 1.20 to 2.07 in the proven fertile group and from 0 to 2.28 in infertile group. Conclusion: SDI was significantly less in fertile men. It is suggested that SDI should also be used to differentiate between fertile and infertile males in addition to other semen parameters as it can be useful in identifying potential infertile males.